Draft Five Year Plan 1978-83 Centrally Sponsored Schemes Union Territory of Pondicherry - Planning Commission (Planning Commission, 1978)
The main object of the scheme is to link in the programme of Production inputs fifth that of the Technical knowhow through a well organised institutional, field training programmes -and formation of informal voluntary, groups to one the most efficient handling of the scarce input s secured at considerable cost. the training is intended to acquaint the farmers, fam women and young farmers of the various needs of prediction -requisites available, to provide adequate knowledge of the inputs and also enable them to develop skills to handle the in most efficiently for the maximum possible advantages.
Government of Pondicherry Planning and Research Department